Twelve-year outcomes of bedside laser photocoagulation for severe retinopathy of prematurity - Bingzhi Yang; Chaohui Lian; Ruyin Tian; Yi Chen; Song Tang; Haishan Xiang; Honghui He; Guoming Zhang (Frontiers Media S.A., 2023)
PurposeThe purpose of this study is to evaluate the 12-year outcomes of bedside laser photocoagulation (LP) for severe retinopathy of prematurity (ROP) under sedation combined with ocular surface anesthesia in neonatal intensive care units (NICU).DesignThe study is a retrospective case series.MethodsInfants treated with bedside LP for severe ROP from April 2009 to September 2021 were included. All LP treatments were performed under sedation and surface anesthesia at the bedside in NICU. Data were recorded for clinical and demographic characteristics, total laser spots, duration of treatment, proportion of total regression of ROP, proportion of recurrence, and adverse events.ResultsA total of 364 infants (715 eyes) were included, with a mean gestational age of 28.6 ± 2.4 weeks (range: 22.6-36.6 weeks) and a mean birth weight of 1,156.0 ± 339.0 g (range: 480-2,200 g). The mean number of laser spots was 832 ± 469, and the mean duration of treatment was 23.5 ± 5.3 min per eye. Of all the eyes, 98.3% responded to LP with complete regression of ROP. ROP recurred in 15 (2.1%) eyes after the initial LP. Additional LP was performed in seven (1.0%) eyes. No patient exhibited mistaken LP of other ocular tissues, and there were no serious ocular adverse effects. None of them needed endotracheal intubation.ConclusionsBedside LP treatment is effective and safe for premature infants with severe ROP under sedation and surface anesthesia in NICU, especially for infants whose general condition is unstable and not suitable for transport.